Promising tools into oxidative stress: A review of non-rodent model organisms - Yuhao Zhang; Yun Li; Tianyi Ren; Jin-ao Duan; Ping Xiao (Redox Biology, 2024)
Oxidative stress is a crucial concept in redox biology, and significant progress has been made in recent years. Excessive levels of reactive oxygen species (ROS) can lead to oxidative damage, heightening vulnerability to various diseases. By contrast, ROS maintained within a moderate range plays a role in regulating normal physiological metabolism. Choosing suitable animal models in a complex research context is critical for enhancing research efficacy. While rodents are frequently utilized in medical experiments, they pose challenges such as high costs and ethical considerations. Alternatively, non-rodent model organisms like zebrafish, Drosophila, and C. elegans offer promising avenues into oxidative stress research. These organisms boast advantages such as their small size, high reproduction rate, availability for live imaging, and ease of gene manipulation. This review highlights advancements in the detection of oxidative stress using non-rodent models. The oxidative homeostasis regulatory pathway, Kelch‐like ECH‐associated protein 1-Nuclear factor erythroid 2-related factor 2 (Keap1-Nrf2), is systematically reviewed alongside multiple regulation of Nrf2-centered pathways in different organisms. Ultimately, this review conducts a comprehensive comparative analysis of different model organisms and further explores the combination of novel techniques with non-rodents. This review aims to summarize state-of-the-art findings in oxidative stress research using non-rodents and to delineate future directions.